ASSA13-11-8 Age and Gender Association Between Microalbuminuria and Arterial Stiffness in a Chinese Population Based Study. (29th April 2013) - Yao, Lu; Hong, Yuan; Ying, Li; Zhijun, Huang
Abstract : Background and Objective: Microalbuminuria (MAU) is recognised as a marker of vascular dysfunction. Brachial-ankle pulse wave velocity (baPWV) reflects the stiffness of central and peripheral muscular arteries. Although several studies have reported the relationship between them, but there are no reports of their significance, and also age and gender association between arterial stiffness (AS) and MAU in Chinese population. This study aimed to assess the association between MAU and AS, and also age and gender association between MAU and AS in a Chinese population in the middle area of China. Methods: A total of 6783 subjects, 3618 man and 3165 women aged 20–80 years, were recruited and stratified on the basis of age and gender. All participants underwent the measurement of waist circumference, blood pressure (BP), baPWV, blood and urine chemistry. Within albuminuria, urinary ACR ranging from 30 to 300μg/mg was defined as MAU, . Logistic regression was used to evaluate the relationship between MAU and baPWV, among the patients 1664 had MAU. Results: After adjusting for mean arterial pressure, fasting glucose, chronic kidney disease, smoking, alcohol drinking, and physical activity status, multiple logistic regression analyses revealed people in baPWV group were significantly associated with MAU (P < 0.001) compared with the normoalbuminuria, the MAU patients also had a significantly lower high density lipoprotein concentration (P < 0.005), and more elder people had MAU (P < 0.001). More man had MAU (P = 0.005) and higher but not significant baPWV (P < 0.05) than women. Conclusions: These findings demonstrate great evidence for the association between AS and MAU and also age and gender dependent association of AS and MAU, suggesting that age and gender should be taken into accounted in the management of MAU and AS aiming to reduce subclinical target organ damage.